PENERAPAN METODE COMPUTER ASSISTED LEARNING (CAL) TEKNIK AKUPRESUR PADA IBU MENYUSUI BERBASIS MULTIMEDIA INTERAKTIF - Rimmar Siringoringo (LPPM Politeknik LP3I Medan, 2020)
One of the causes of the increase in Infant Mortality Rate (IMR) is the decrease factor in exclusive breastfeeding to infants. Based on the Statistics Center (BPS) in 2016 covering 49.51% of infants in Indonesia who received exclusive breastfeeding less than 6 months. In this case, multimedia technology can be used to support government programs in Increasing Exclusive ASI Coverage Rates for Indonesian children in accordance with Government Regulation No. 33 of 2012. So, the researchers conducted research using computer-based multimedia learning assistance (CAL) technology for help support the health of several posyandu, puskesmas, and mother and child clinics in promoting exclusive breastfeeding through the Acupressure Technique which can be accessed through the release of the hormone prolactin and the hormone oxytocin in drinking mothers. This multimedia application based on Computer Assisted Learning (CAL) can provide understanding and learning about Acupressure Techniques with visuals that are interesting, easy to understand, and supported by clear audio visuals.